Pendampingan Hukum Bagi Pemilik Spam Pematang Rahim Dalam Kontrak Dan Perjanjian - Hasan Basri; Sayida Khoiratun Nisak; Kurniawan; Sitii Fatimah; Sarni (CV. Akira Java Bulu, 2025)
This community service activity aims to enhance the legal understanding of the managers and owners of the Drinking Water Supply System (SPAM) in Pematang Rahim Village regarding the drafting of contracts and cooperation agreements with third parties. The main issue faced by the partners is the lack of understanding of formal legal aspects in every collaboration, which often leads to potential disputes and imbalances in rights and obligations. Through a participatory-based legal mentoring approach, participants were provided with training, simulations, and assistance in drafting contracts in accordance with legal regulations. The results of the activity showed a significant improvement in various aspects of the participants’ legal competence. Based on the evaluation, understanding of contract elements and the principles of contract law increased by 85%, as reflected in the post-test results and participants’ ability to identify the legal components of a valid agreement under civil law. Furthermore, practical skills in drafting valid and binding written agreements improved by 80%, as demonstrated by the quality of cooperation contract drafts prepared by participants during the mentoring sessions. This improvement also had a positive impact on SPAM’s institutional governance, where the level of transparency and accountability increased by 75%, accompanied by the application of justice principles in decision-making and the distribution of responsibilities among parties. Overall, this community service activity had a tangible impact on strengthening SPAM’s institutional governance to become more professional, transparent, accountable, and equitable, while also fostering an adaptive and sustainable legal culture at the village level.